2003
DOI: 10.1017/s0022112003004993
|View full text |Cite
|
Sign up to set email alerts
|

Non-circular baroclinic beta-plane modons: constructing stationary solutions

Abstract: Conditions determining the existence of localized steadily translating two-layer vortices (modons) of arbitrary symmetric form on the $\beta$-plane are considered. A numerical method for direct construction of modon solutions is suggested and its accuracy is analysed in relation to the parameters of the computational procedure and the geometrical and physical parameters of the modon sought. Using this method, several non-circular baroclinic solutions are constructed marked by nonlinearity of the dependence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…The first one is the reviled dependence of the dipole stability on the separation between the patches in all kinds of stationary dipoles: larger separation guarantees resistance to stronger perturbations. Such dependence has been observed in baroclinic modons and distributed hetons whose two vorticity 'masses' can overlap (Sokolovskiy & Verron 2000;Kizner et al 2002, Kizner, Berson & Khvoles 2003Kizner 2006Kizner , 2008. Here we have shown that the same is valid for non-overlapping barotropic dipoles.…”
Section: Resultssupporting
confidence: 78%
“…The first one is the reviled dependence of the dipole stability on the separation between the patches in all kinds of stationary dipoles: larger separation guarantees resistance to stronger perturbations. Such dependence has been observed in baroclinic modons and distributed hetons whose two vorticity 'masses' can overlap (Sokolovskiy & Verron 2000;Kizner et al 2002, Kizner, Berson & Khvoles 2003Kizner 2006Kizner , 2008. Here we have shown that the same is valid for non-overlapping barotropic dipoles.…”
Section: Resultssupporting
confidence: 78%
“…To summarize, this vortical structure appears similar to the elliptical two-layer modons constructed by Kizner et al, 11 and can be considered a distributed ͑and smooth͒ analog of hetons.…”
Section: B Transitions In Modonssupporting
confidence: 64%
“…However, numerical experiments showed that barotropic and baroclinic solutions with such a discontinuity are strongly unstable. [9][10][11] A heton is essentially baroclinic. It is comprised of two discrete vortices of equal strength but opposite signs confined to different layers of a two-layer fluid, and typically separated by a certain distance.…”
Section: A Baroclinic Modons and Hetonsmentioning
confidence: 99%
See 2 more Smart Citations